Enhanced Antimalarial Therapy Using Mefloquine and Artesunate in the Treatment of Uncomplicated Plasmodium falciparum - Saeheng , Teerachat; Na-Bangchang, Kesara (New Advances in Medicine and Medical Science Vol. 8, 2023)
The current study aimed to investigate promising alternative regimens of artesunate-mefloquine with improved efficacy to cope with multidrug resistant P. falciparum. Malaria-related mortality has tremendously reduced during the last two decades since the introduction of artemisinin-based combination therapy (ACT). Data from the previously published article on the clinical efficacy of the three-day artesunate-mefloquine combination in the Thai-Myanmar borders during 2008-2009 were used for pharmacokinetic-pharmacodynamic (PK/PD) analysis. All patients were treated with a three-day combination of artesunate-mefloquine. Population PK-PD models were developed. Data from clinical observations were used to validate the developed models. Based on mefloquine sensitivity, patient adherence, and parasite biomass, simulations of the clinical efficacy of alternative mefloquine regimens were carried out. The created PK/PD models are well described with data from clinical observations. For mefloquine-resistant P. falciparum, a three-day standard regimen of artesunate-mefloquine is suitable (>50% efficacy) only when the level of parasite sensitivity was < 1.5-fold of the cut-off level (IC50 < 36 nM). For mefloquine-sensitive parasites with IC50 < 23.19 nM (0.96-fold), all regimens provided satisfactory efficacy. In the isolates with IC50 of 24 nM, regimen-I is recommended. Curative treatment criteria for mefloquine and artesunate were C336h (>408 ng.mL-1) or Cmax/IC50 (>130.1 g.m/M) and Cmax/IC50 (>381.2 g.m/M), respectively. A three-day artesunate-mefloquine is suitable for mefloquine-resistant P. falciparum with IC50 of < 36 nM. Efficacy of the reduced dose regimens is satisfactory only when IC50 was < 24 nM.